Challenges with defining response to antitumor agents in pediatric neuro‐oncology: A report from the response assessment in pediatric neuro‐oncology (RAPNO) working group. Issue 9 (26th April 2013) - Warren, Katherine E.; Poussaint, Tina Y.; Vezina, Gilbert; Hargrave, Darren; Packer, Roger J.; Goldman, Stewart; Wen, Patrick Y.; Pollack, Ian F.; Zurakowski, David; Kun, Larry E.; Prados, Michael D.; Rutkowski, Stefan; et al.
Abstract Criteria for new drug approval include demonstration of efficacy. In neuro‐oncology, this is determined radiographically utilizing tumor measurements on MRI scans. Limitations of this method have been identified where drug activity is not reflected in decreased tumor size. The RANO (Response Assessment in Neuro‐Oncology) working group was established to address limitations in defining endpoints for clinical trials in adult neuro‐oncology and to develop standardized response criteria. RAPNO was subsequently established to address unique issues in pediatric neuro‐oncology. The aim of this paper is to delineate response criteria issues in pediatric clinical trials as a basis for subsequent recommendations. Pediatr Blood Cancer 2013;60:1397–1401. © 2013 Wiley Periodicals, Inc.